In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Multidrug-resistant Gram-negative clinical isolates with reduced susceptibility/resistance to cefiderocol: which are the best present and future therapeutic alternatives? - Christophe Le Terrier; Samanta Freire; Patrice Nordmann; Laurent Poirel (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose To evaluate the different present and future therapeutic β-lactam/β-lactamase inhibitor (BL/BLI) alternatives, namely aztreonam-avibactam, imipenem-relebactam, meropenem-vaborbactam, cefepime-zidebactam, cefepime-taniborbactam, meropenem-nacubactam, and sulbactam-durlobactam against clinical isolates showing reduced susceptibility or resistance to cefiderocol in Enterobacterales, Acinetobacter baumannii , and Pseudomonas aeruginosa. Methods MIC values of aztreonam, aztreonam-avibactam, cefepime, cefepime-taniborbactam, cefepime-zidebactam, imipenem, imipenem-relebactam, meropenem, meropenem-vaborbactam, meropenem-nacubactam, sulbactam-durlobactam, and cefiderocol combined with a BLI were determined for 67, 9, and 11 clinical Enterobacterales, P. aeruginosa or A. baumannii isolates, respectively, showing MIC values of cefiderocol being ≥1 mg/L. If unavailable, the respective β-lactam breakpoints according to EUCAST were used for BL/BLI combinations. Results For Enterobacterales, the susceptibility rates for aztreonam, cefepime, imipenem, and meropenem were 7.5%, 0%, 10.4%, and 10.4%, respectively, while they were much higher for cefepime-zidebactam (91%), cefiderocol-zidebactam (91%), meropenem-nacubactam (71.6%), cefiderocol-nacubactam (74.6%), and cefiderocol-taniborbactam (76.1%), as expected. For P. aeruginosa isolates, the higher susceptibility rates were observed for imipenem-relebactam, cefiderocol-zidebactam, and meropenem-vaborbactam (56% for all combinations). For A. baumannii isolates, lower susceptibility rates were observed with commercially or under development BL/BLI combos; however, a high susceptibility rate (70%) was found for sulbactam-durlobactam and when cefiderocol was associated to some BLIs. Conclusions Zidebactam- and nacubactam-containing combinations showed a significant in vitro activity against multidrug-resistant Enterobacterales clinical isolates with reduced susceptibility to cefiderocol. On the other hand, imipenem-relebactam and meropenem-vaborbactam showed the highest susceptibility rates against P. aeruginosa isolates. Finally, sulbactam-durlobactam and cefiderocol combined with a BLI were the only effective options against A. baumannii tested isolates.